2002
DOI: 10.1108/09604520210442119
|View full text |Cite
|
Sign up to set email alerts
|

Service quality in a cellular telecommunications company: a South African experience

Abstract: This study deals with the measurement of service quality at cellular retail outlets in the South African environment. The focus is on perception and expectation of service quality from the customer’s perspective. A literature review was conducted on, models of measurement for service quality. The research was conducted via a structured questionnaire based on the SERVQUAL model. Primary data was gathered via telephonic interviews from a sample of 583 customers. The total scale reliability for this study is 0.95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(59 citation statements)
references
References 13 publications
0
56
0
Order By: Relevance
“…Even the limited application of the SERVQUAL model in healthcare research has enabled health organizations to improve service quality (Van Der Wal et al, 2002). In two studies that examined the effectiveness of service quality and customer satisfaction, Curry and Sinclair (2002) and Boshoff and Gray (2004) respectively report that the SERVQUAL model was also successful in determining customer loyalty.…”
Section: Perceived Service Qualitymentioning
confidence: 99%
“…Even the limited application of the SERVQUAL model in healthcare research has enabled health organizations to improve service quality (Van Der Wal et al, 2002). In two studies that examined the effectiveness of service quality and customer satisfaction, Curry and Sinclair (2002) and Boshoff and Gray (2004) respectively report that the SERVQUAL model was also successful in determining customer loyalty.…”
Section: Perceived Service Qualitymentioning
confidence: 99%
“…5) Empathy: the level of caring and individualized attention that the firm provides to its customers. SERVQUAL has been used to measure service quality in a wide range of service industries, which included; Health care sector (Carman, 1990;Headley & Miller, 1993); Fast food (Lee & Ulgado, 1997); Banking (Lam, 2002), telecommunications (Wal, Pampallis, & Bond, 2002); Information systems (Jiang, Klein, & Crampton, 2000) and retail chain (Parasuraman, Zeithaml, & Berry, 1994). Despite, the widespread use of the SERVQUAL to measure service quality, several applications of the scale in different service settings have shown that the type and number of dimensions actually varies, depending on the service under investigation (Akbaba, 2006;Ladhari, 2009).…”
Section: Perceived Service Qualitymentioning
confidence: 99%
“…On the basis of this methodology, several quality assessment mechanisms have been developed and obtained good acceptance levels in different sectors: education [6], banking [7] [8], telecommunications [9], health care [10] [11], public services [12] [13], professional services [14], retail [15], transport and delivery [16], finance [17], tourism and hotels [18], digital libraries [19], web services [20] and military and medical air transport [21].…”
Section: Introductionmentioning
confidence: 99%